Sepsis and Its impact on outcomes in elderly patients admitted to a Malaysian intensive care unit - Wan Shukeri, Wan Fadzlina; Mat Nor, Mohd Basri; Md Ralib, Azrina (Penerbit Universiti Sains Malaysia, 2022)
Sepsis is an important cause of morbidity and mortality in elderly patients, but there is a scarcity of data on sepsis in this specific cohort. We performed this study to review the impact of sepsis on outcomes in elderly patients admitted to our local intensive care unit (ICU). This was a secondary analysis of prospectively collected data of 159 consecutive adult patients with sepsis admitted to an ICU of a tertiary hospital in Malaysia over a three-year period. Of the 159 patients analysed, elderly patients constituted 18.9% of the cohort. Fifty percent of the older patients died within 30 days, compared to 24% of younger patients (P = 0.005). On multivariate analysis, old age was found to be independently predictive of 30-day mortality with an adjusted odds ratio (OR) of 2.5 (95% confidence interval [CI]: 1.05, 6.01) compared to younger patients (P = 0.021). In a Kaplan-Meier analysis, survival probability was significantly lower in patients of an older age compared to younger patients (P = 0.015). In conclusion, mortality from sepsis is considerably higher in elderly patients, with age as an independent risk factor for mortality.